2022
DOI: 10.1007/s00432-022-04545-6
|View full text |Cite
|
Sign up to set email alerts
|

Developing a primary tumor and lymph node 18F-FDG PET/CT-clinical (TLPC) model to predict lymph node metastasis of resectable T2-4 NSCLC

Abstract: Purpose The goal of this study was to investigate whether the combined PET/CT radiomic features of the primary tumor and lymph node could predict lymph node metastasis (LNM) of resectable non-small cell lung cancer (NSCLC) in stage T2-4. Methods This retrospective study included 192 NSCLC patients who underwent tumor and node dissection between August 2016 and December 2017 and underwent 18F-fluorodeoxyglucose (18F-FDG) PET/CT scanning 1–3 weeks before sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The clinical outcome of NSCLC is directly related to its stage at diagnosis [ 43 ]. Moreover, there were reports showing the usefulness of the 18 F-FDG PET/CT radiomics-based ML method for predicting tumor stage in lung cancer [ 44 46 ]. Wang et al [ 44 ] reported that the ML model with the gradient tree boosting (XGB) ML algorithm using combined clinical data and PET/CT radiomics of the primary tumor and lymph node had the highest diagnostic performance in predicting lymph node metastasis (LNM) in NSCLC (AUC: 0.93).…”
Section: Clinical Application Of 18 F-fdg Pet/ct R...mentioning
confidence: 99%
“…The clinical outcome of NSCLC is directly related to its stage at diagnosis [ 43 ]. Moreover, there were reports showing the usefulness of the 18 F-FDG PET/CT radiomics-based ML method for predicting tumor stage in lung cancer [ 44 46 ]. Wang et al [ 44 ] reported that the ML model with the gradient tree boosting (XGB) ML algorithm using combined clinical data and PET/CT radiomics of the primary tumor and lymph node had the highest diagnostic performance in predicting lymph node metastasis (LNM) in NSCLC (AUC: 0.93).…”
Section: Clinical Application Of 18 F-fdg Pet/ct R...mentioning
confidence: 99%
“… 70 Similar studies were also conducted based on other solid tumors such as lung cancer and gastric cancer. 71 , 72 In another study published in May 2023, Zhao et al 73 tried building a radiomic model using image features derived from different tissues including visceral metastasis, bone metastasis or nodal metastasis to predict immune therapy in advanced breast cancer. The result showed that the radiomic model obtained a high accuracy with an AUC of 0.994 (95% CI: 0.988 to 1.000) in the training cohort, and 0.920 (95% CI: 0.824 to 1.000) in the validation cohort, respectively.…”
Section: Radiomic Studies Regarding the Tme Reveal Crucial Biomarkers...mentioning
confidence: 99%
“…Nonetheless, histopathological evaluation often necessitates invasive procedures, which patients may sometimes be unable to tolerate. Furthermore, even upon successful completion of surgery, false-negative results are not uncommon in such procedures [10,11]. Currently, 18 F-fuorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) is considered the most accurate imaging modality for diagnosing FUO [12][13][14][15], as it allows for diagnosis from both metabolic and morphological perspectives, particularly facilitating the diagnosis, staging, and assessment of therapeutic e cacy in lymphoma.…”
Section: Introductionmentioning
confidence: 99%